Page 13 - Bahan Ajar Berbasis Flipped Learning pada materi Diferensial
P. 13

Penyelesaian

                         a.     =   (2   + 1)

                              Misal:     =    →    = 1
                                                ′
                                        = 2   + 1 →    = 2
                                                     ′
                              Jadi jika     =    .   , maka     ′  =    ′     +       ′

                                                            ′
                                                              = 1. (2   + 1) +   . 2
                                                            ′
                                                              = 2   + 1 + 2  
                                                            ′
                                                              = 4   + 1 atau        = 4   + 1
                                                                                
                                              2
                         b.     = 4(5   + 3)  
                                            2
                                                  ′
                              Misal:     = 4   →    = 8  
                                        = 5   + 3 →    = 5
                                                     ′
                              Jadi jika     =    .   , maka     ′  =    ′     +       ′

                                                            ′
                                                              = 8  . (5   + 3) + (4   ). 5
                                                                                   2
                                                                                   2
                                                                    2
                                                            ′
                                                              = 40   + 24   + 20  
                                                            ′
                                                                    2
                                                                                         2
                                                              = 60   + 24 atau        = 60   + 24
                                                                                    
                         c.     = (2   + 1)(   − 4)
                                                     ′
                              Misal:     = 2   + 1 →    = 2
                                                    ′
                                        =    − 4 →    = 1
                              Jadi jika     =    .   , maka     ′  =    ′     +       ′
                                                            ′
                                                              = 2. (   − 4) + (2   + 1). 1
                                                            ′
                                                              = 2   − 8 + 2   + 1
                                                            ′
                                                              = 4   − 7 atau        = 4   − 7
                                                                                


                         d.     = (   − 5)(2   − 7)
                                     2
                              Misal:     =    − 5 →    = 2  
                                                     ′
                                           2
                                                     ′
                                        = 2   − 7 →    = 2
                              Jadi jika     =    .   , maka     ′  =    ′     +       ′

                                                              = 2  . (2   − 7) + 2. (   − 5)
                                                            ′
                                                                                    2
                                                                                2
                                                            ′
                                                              = 4   − 14   + 2   − 10
                                                                   2


               12 | T u r u n a n                                                      K e l a s   X I   S M A
   8   9   10   11   12   13   14   15   16   17   18